Finance and Development, March 1986. (Finance and Development; Finance and Development, 1986)
This paper examines adjustment, growth, and the IMF's role. Under the Baker plan, the IMF would continue to play a central role in dealing with the economic imbalances and the debt problems that countries face, a role that would continue to include the analysis and policy advice that the IMF brings to discussions with member countries. The IMF's role will also be to continue to help countries obtain new external financing from commercial banks as well as from official sources.